Wastes released by tanneries at Patrocinio Paulista, São Paulo State, Brazil - Bonotto, Daniel Marcos [UNESP]; Jimenez-Rueda, J. R. [UNESP]; Palermo, H. F. [UNESP]; Caprioglio, L. [UNESP] (Wit Press, 2010)
This investigation was carried out within the Parana sedimentary basin, Brazil, and involved the sampling of sludge and residuary waters that were collected from reservoirs/decantation ponds settled in two tanneries situated at Patrocinio Paulista, São Paulo State Two samples from each tannery were collected, stored in appropriate flasks and transported to the LABIDRO for chemical analysis The LABIDRO (Laboratory of Isotopes and Hydrochemistry) of the Petrology Department at the Geosciences and Exacts Sciences Institute of UNESP is situated in Rio Claro city, about 240 km distant from the investigated area The data for residuary waters were compared with guideline values established by two different legislations (a) Rule No 12486 (NTA60) established in 20(th) October 1978 by São Paulo State for defining the potable water standards and (b) Register 997 published on 31 May 1976 that defines the permissible concentration limits in effluents to be released to water bodies (coastal, fresh or ground water) in São Paulo State The results confirmed that leather production is an activity with high environmental impact, despite improvements that may be achieved by tanneries
Keywords: leather; tanneries sludge; residuary waters; São Paulo State Brazil